Downregulation of CCL20 in Severe COVID-19 Infections and its Association with NLRP3 Gene Polymorphisms - Maeh, Raghad KH.; Fadhil, Hula Y. (Iraqi Journal of Science, 2025)
Genetic factors are associated with the immunogenicity of coronavirus disease 2019 (COVID-19). This association reaches the level of cellular processes such as autophagy, ferroptosis, and pyroptosis, correlating with increased activity of the Nod-like receptor family, pyrin domain containing 3 (NLRP3) inflammasome. The present study focuses on exploring the linkage between severe COVID-19, CCL20 chemokines, and NLRP3 gene variants in an Iraqi sample. A case-control study enrolled 99 COVID-19 patients and 96 controls and measured CCL20 levels, disease severity, blood biomarkers, and NLRP3 SNPs (rs35829419, rs10754558, rs72771992, and rs10802501) using allele-specific primer methods. The results showed that the frequencies of NLRP3 rs35829419 A allele (28.8 vs. 18.8 %; OR= 1.75; 95% CI = 1.09-2.81 ; p < 0.013) and genotype CA (45.5 vs 30.5 %; OR=1.82; 95% CI =1.01-3.26 ; p <0.032) are related to susceptibility to COVID-19. The median value of CCL20 in severe COVID-19was 70.7 (range 63.4 – 81.6), being significantly lower than that in moderate cases (median 85.2; range 67.1 – 96.2). A negative correlation also existed between CCL20 and the levels of the inflammatory markers, such as ferritin, CRP, LDH, and D-dimer. The analysis of the relationship between the frequencies of NLRP3 SNPs alleles and genotypes with CCL20 level showed that the increases in the frequencies of rs10754558 C allele and CC genotype were correlated with the high median value of the CCL20 level compared with the low median value (48.8 vs. 33.3 %; OR=1.9; 95% CI = 1.24-2.91; p < 0.004 for the allele and 40.7 vs. 28.3%; OR= 2.05; 95% CI = 1.07-3.93; p < 0.033 for the genotype). Median levels of CCL20 stratified by SNP genotypes in the NLRP3 gene showed no significant relationship, except rs10802501 (81.58 vs 88.61 for AA genotype; 74.29 vs 81.58 for TT genotype; p=0.045). The study showed that the associations of several NLRP3 SNPs with altered CCL20 and other chemokines’ levels can provide information about cellular inflammatory mechanisms that will be instrumental during making precise decisions for the treatment of disease.